Investigation of Proposed Mechanisms of Chemotherapy-Induced Venous Thromboembolism: Endothelial Cell Activation and Procoagulant Release Due to Apoptosis. (July 2015) - Kirwan, Cliona C.; McCollum, C. N.; McDowell, G.; Byrne, G. J.
Venous thromboembolism (VTE) during chemotherapy is common, with 7% mortality in metastatic breast cancer (MBC). In a prospective cohort study of patients with breast cancer, we investigated whether vascular endothelial cell activation (VECA), and whether apoptosis, is the cause of chemotherapy-induced VTE.Methods: Serum markers of VECA, E-selectin (E-sel), vascular cell adhesion molecule 1 (VCAM-1) andd -dimer (fibrin degradation and hypercoagulability marker) were measured prechemotherapy and at 1, 4, and 8 days following chemotherapy. Clinical deep vein thrombosis (DVT) or pulmonary embolism and occult DVT detected by duplex ultrasound imaging were recorded as VTE-positive (VTE+). In patients with MBC, hypercoagulable response to chemotherapy was compared between patients with and without cancer progression. Development of VTE and cancer progression was assessed 3 months following starting chemotherapy.Results: Of the 134 patients, 10 (7.5%) developed VTE (6 [17%] of 36 MBC receiving palliation, 0 of 11 receiving neoadjuvant to downsize tumor, and 4 [5%] of 87 early breast cancer receiving adjuvant chemotherapy, P = .06). Levels of E-sel and VCAM-1 decreased in response to chemotherapy ( P < .001) in both VTE+ and patients not developing VTE (VTE−). However, decrease in VECA markers was similar in VTE+ and VTE− patients, implying this is not the cause of VTE. In patients with MBC following chemotherapy, d -dimer (geometric mean) increased by 36% in the 21 patients with MBC responding to chemotherapy but steadily decreased by 11% in the 15 who progressed (day 4, P < .01), implying patients with tumor response (apoptosis) had an early hypercoagulable response.Conclusions: During chemotherapy for breast cancer, VECA is induced; however, this is not the primary mechanism for VTE. Chemotherapy-induced apoptosis may enhance hypercoagulability and initiate VTE.